Transformation of remote personnel management methods under the conditions of marital state - Hordiienko , Yevheniya; Kozhurina , Vira (Pressing Problems of Public Administration, 2024)
The article reveals the essence of remote work and remote personnel management under martial law. The main idea of the paper is to identify and analyse changes that have occurred in personnel management methods due to the need for a mass transition to remote work in wartime conditions. The authors consider both general trends (related to the development of technologies and experience of working during quarantine restrictions) and specific ones (inherent specifically to the Ukrainian economy under martial law). On the basis of a detailed analysis, the main key problems of the Ukrainian labour market in the conditions of martial law and their impact on the implementation of personnel management are highlighted. The prerequisites for the introduction of a remote form of employment in Ukraine are disclosed, and it is proposed to classify them into general (inherent in all world markets) and special (typical for Ukraine and a response to challenges related to military aggression). Opportunities for employers and employees provided by remote work are indicated. A review of the experience of countries with advanced management technologies and a long-term state of permanent military operations, which have cases of developed methods in the field of overcoming the consequences of war, and the experience of international companies implementing advanced personnel management methods, was conducted. Emphasis is placed on the need to develop practical recommendations for the use of modern methods and a wide range of personnel management tools in modern Ukrainian conditions. On the basis of the analysis of the achievements of domestic companies, the strengthening of the importance of methods of motivation, adaptation and prevention of stress, burnout and depression is substantiated in view of the negative consequences of such psychological problems for achieving the goals of the organization. On the basis of the generalization of the main theoretical approaches, the point of view regarding remote work, the importance of strengthening the adaptation of personnel to new operating conditions, the development of a number of motivational measures and the need to ensure the mobility of the workforce is substantiated.